Groundwater Management Protection Program for Nigeria - Nwankwo Nnabueze Kalu (RUDN Journal of Ecology and Life Safety, 2018)
This article looks into groundwater pollution in Nigeria; groundwater uses and suggests how to go about protection of Nigerias underground water. There were case studies of wells at different regions; content analysis indicated physical, chemical and organic factors with parameters that surpassed upper boundaries established by World Health Organization. The public full understanding of economic and social importance of underground water will help in Full integration of Comprehensive Regional Groundwater Protection Program for Nigeria.